Organising Pneumonia in a Patient Following Obinutuzumab for Follicular Lymphoma - Viral Nanda; Huw Ellis; Harshana Bandara (Respirology Case Reports, 2025)
ABSTRACT Hereby presenting a patient with follicular lymphoma, treated with obinutuzumab subsequently developing organising pneumonia. The case highlights newer generation culprits causing pulmonary complications and the importance of vigilant imaging survey and timely treatment to prevent the fibrotic progression in these patients.